2006
DOI: 10.1111/j.0014-3820.2006.tb01222.x
|View full text |Cite
|
Sign up to set email alerts
|

MULTITRAIT EVOLUTION IN LINES OFDROSOPHILA MELANOGASTERSELECTED FOR INCREASED STARVATION RESISTANCE: THE ROLE OF METABOLIC RATE AND IMPLICATIONS FOR THE EVOLUTION OF LONGEVITY

Abstract: Abstract. Starvation resistance is a trait often associated with longevity. Animals with increased longevity frequently show elevated starvation resistance and vice versa. Consequently, both life-history traits are thought to share genetic and physiological mechanisms, such as increased fat content and lowered metabolic rate. Here, we present results from 20 generations of selection on Drosophila melanogaster for increased starvation resistance at the time of adult eclosion. We observe that starvation resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Previously, our laboratory has selected four lines for increased starvation resistance (SR) and maintained two control lines (C) in a 20 generation experiment [28]. We chose a single replicate line of each selection regime to perform the microarray experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our laboratory has selected four lines for increased starvation resistance (SR) and maintained two control lines (C) in a 20 generation experiment [28]. We chose a single replicate line of each selection regime to perform the microarray experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, we previously selected Drosophila for increased starvation resistance (SR) and maintained corresponding control lines under optimal food (C) [28]. The selection resulted in SR lines with not only elevated resistance to starvation but also extended lifespan under three other food levels as compared with the C flies.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these data suggest that there is little or no specific dynamic action (SDA) in either the short- or long-term. In contrast to these findings, Baldal et al reported lowered metabolic rate as a result of starvation but, in the long-term across generations, elevated metabolic rates associated with starvation resistance (Baldal et al, 2006). Again, variation exists in the literature, with another long-term study reporting no change in metabolic rate produced by chronic diet restriction (Hulbert et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Investigators have long used the fruit fly as a model for investigations of life span, and accordingly have measured metabolic rate in an often unsuccessful attempt to correlate metabolism to longevity (Arking et al, 1988; Baldal et al, 2006; Hulbert et al, 2004; Khazaeli et al, 2005; Melvin et al, 2007; Miquel et al, 1982; Partridge et al, 2005; Promislow and Haselkorn, 2002; Van Voorhies et al, 2003, 2004b). Metabolic rate in Drosophila has also been investigated in the context of specific genotypes (Hoekstra and Montooth, 2013; Jensen et al, 2014; Jumbo-Lucioni et al, 2010; Montooth et al, 2003; Stone et al, 2013), to reveal how genotype underpins specific metabolic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably this response is quite different from the evolutionary response to acute starvation during adulthood. Rather than speeding up developmental time and decreasing size, as is the case for larval malnutrition, selection on starvation resistance in young adulthood generally selects for slower development and increased lipid accumulation, resulting in larger adult size (Baldal et al 2006;Bubliy & Loeschcke 2005;Chippindale et al 1996) (but see Hoffmann et al 2005). This difference highlights the fact that similar selection pressures may select for different adaptations depending on when in life they are experienced.…”
Section: Introductionmentioning
confidence: 99%